2010
DOI: 10.1108/15736101011068037
|View full text |Cite
|
Sign up to set email alerts
|

A finite element analysis of pneumatic‐tire/sand interactions during off‐road vehicle travel

Abstract: Purpose -The purpose of this paper is to carry out a series of transient, non-linear dynamics finite element analyses in order to investigate the interactions between a stereotypical pneumatic tire and sand during off-road vehicle travel. Design/methodology/approach -The interactions were considered under different combined conditions of the longitudinal and lateral slip as encountered during "brake-and-turn" and "drive-and-turn" vehicle maneuvers. Different components of the pneumatic tire were modeled using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…There is a long-standing interest to better understand mobility in granular environments within both the robotics and granular physics communities. [1][2][3][4][5][6][7][8][9] This is important for new mobility and material transfer solutions, particularly in the space sector where increased mass and volume are oen costly while increased moving parts or complexity are regarded as increasing risk. This complexity is further compounded by the variety of granular materials which exist.…”
Section: Introductionmentioning
confidence: 99%
“…There is a long-standing interest to better understand mobility in granular environments within both the robotics and granular physics communities. [1][2][3][4][5][6][7][8][9] This is important for new mobility and material transfer solutions, particularly in the space sector where increased mass and volume are oen costly while increased moving parts or complexity are regarded as increasing risk. This complexity is further compounded by the variety of granular materials which exist.…”
Section: Introductionmentioning
confidence: 99%
“…Compaction (Grujicic et al, 2008a(Grujicic et al, , b, 2009(Grujicic et al, , 2010 Compaction (Grujicic et al, 2008a(Grujicic et al, , b, 2009(Grujicic et al, , 2010 Hydro (Grujicic et al, 2008a(Grujicic et al, , b, 2009(Grujicic et al, , 2010 Geometrical instantaneous strain Table II.…”
Section: Effect Of Up-armoring Of Hmmwvmentioning
confidence: 99%
“…The tire/sand non-linear force-element model (Grujicic et al, 2010) was implemented as a "utyre_spck.f" user tire-model subroutine in Simpack (Intec, 2008). Within this subroutine, the current values of the wheel-center kinematic parameters (e.g.…”
Section: Effect Of Up-armoring Of Hmmwvmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional sticking stiffness was applied inside the sticking region by default in Abaqus. Xia 33 and Grujicic 38 reported that a constant coefficient of friction could be used for the tyre-soil contact. The coefficient of friction was assumed as 0.6 for the tread-soil contact in this article.…”
Section: Contact Definitionmentioning
confidence: 99%